Evidence of board diversity and shariah committee's attributes of Islamic banks : impacts on performance - Mustapha Usman (2015)
Corporate governance of Islamic banks presents entirely unique and different complexities compared to other conventional institutions. Despite these complexities and some reported cases of financial scandals involving the Islamic banks, studies of the corporate governance of the Islamic banks is still lacking. The research have studied the two most important aspects of corporate governance of Islamic banks namely, Boards (BODs) and Shariah Committees (SC). The study specifically, has examined the extent of diversity in the board and SC attributes governance mechanisms of Islamic banks in Malaysia. It has also examined the impact of board diversity and SC attributes on the performance of the Islamic banks. The sample of the study comprised of the 16 commercial Islamic banks operating in Malaysia over six (6) years from 2008 to 2013. The research used secondary data. Basically, the study used published annual reports of the IBs as the sole source of data. The overall finding revealed that, diversity in the board of the Islamic banks induces better financial performance. Similarly, the research also found gender diversity and multiple directorship of board diversity to be positively linked with the financial performance of the Islamic banks. From the aspect of Shariah compliance, the study found that, the Musharakah and Mudarabah Islamic contracts (PLS) to be improving on the absolute basis from 2008 to 2013. Though, the locally owned Islamic banks appeared to be doing better in musharakah financing. Likewise, the study found a minimal percentage of SC interlock to improve the performance of the Islamic banks. The research concluded that, embracing the idea of diversity in the board, could help in minimizing the complex agency issues between the diverse stakeholders, especially shareholders and Investment Account Holders. Also, regulators like BNM should make further effort to strengthen the function of the SC.